Innovative trends in education policy. (Journal of Educational Sciences, 2016)
Arranged in the article are the factors of innovation in the context of education reforms in Kazakhstan based on legal documents. Also, is shown especially inclusive education in the new century. He explained the role of teacher’s personality, his professional competence, the spiritual wealth in the structure changes in the education system, theinnovative nature of the professional activity of a teacher in close connection with the Bologna process. Novelty in a holistic educational process - the need and demand for the introduction of humanistic values and traditions. Article précised contained innovation and the innovation process. Characterized by cognitive, design, instrumental, correctional components of innovative thinking. Innovation activity according to the author is the driving force, means of introduction of the new into research universities. Offers the experience of American research universities for use in the process of creating a research University. In al-Farabi Kazakh National University analyzed the mechanism of integration of business, employers, science and education. Set out the reasons of influence, a consequence of the resistance of the University staff innovations.Described the innovation process in the system of education from the standpoint of theories and concepts of pedagogical innovation.The proposed innovative environment of a higher educational institution (investors, the Ministry of education and science of the localadministration, resources, staff, technology, consumers of innovative products universities, infrastructure, competitors, intermediaries).The goals of ideas Kaizen system at the methodological level, implemented in order to keep improving the Al- Farabi KazNU, special attention is paid to scientists, scientific schools developing science in the real time.
Keywords: higher education; innovation; innovation environment; innovation process; holistic educational process; innovative thinking; innovative education; the strategy of “Kaizen”; industrial park; business incubator; technology innovation; organizational change